The effect of a high-intensity training unit at a high temperature on weight and some blood components among young freestyle wrestlers - Al Timimi, A. (International Journal of Wrestling Science, 2022)
The aim of this experiment is to know how much the wrestler loses weight compared to some blood components when training at a high intensity in hot weather.